Microwave dielectric properties of Li2M2(MoO4)3 (M = Co, Ni) for LTCC applications - Huang, Cheng‐Liang; Liou, Jie‐Ning; Tsai, Meng‐Hung; Huang, Wen‐Chiao (International journal of ceramic engineering & science, 2020)
Two low‐firing Li2M2(MoO4)3 (M = Co, Ni) dielectrics were prepared, and their microwave dielectric properties were investigated. The XRD patterns indicated both samples crystallized in an orthorhombic structure with different space groups. The microstructures, lattice parameters, and Raman spectra of these ceramics were also systematically studied. The microwave dielectric properties were obtained with εr ~ 9.1, Q × f ~ 34 000 GHz and τf ~ −72 ppm/°C for Li2Co2(MoO4)3 at 840°C, εr ~ 9.6, Q × f ~ 28 000 GHz and τf ~ −71 ppm/°C for Li2Ni2(MoO4)3 at 660°C. With 0.05 mol% Zn substitution, excellent microwave dielectric properties (εr ~ 10.9, Q × f ~ 56 000 GHz and τf ~ −62 ppm/°C) can be obtained for Li2(Ni0.95Zn0.05)2(MoO4)3 at 660°C, indicating a very promising dielectric for LTCC or ULTCC applications at high frequencies. The microwave dielectric properties of two low‐firing Li2M2(MoO4)3 (M = Co, Ni) dielectrics were shown in this manuscript. Excellent microwave dielectric properties (εr ~ 10.9, Q × f ~ 56,000 GHz and τf ~ −62 ppm/°C) can be obtained from Li2(Ni0.95Zn0.05)2(MoO4)3, which indicates a very promising dielectric for LTCC or ULTCC applications at high frequencies..